PERANAN TEKNOLOGI KEUANGAN DALAM MENDUKUNG PERILAKU KEUANGAN GENERASI MUDA DI KABUPATEN BENGKAYANG - Bella Ghia Dimmera; Pramatatya Resindra Widya (JURNAL TRANSFORMATIF UNKRISWINA SUMBA, 2020)
The aim of this study is to explore the behavioral factors of the younger generation in using financial technology applications in their daily lives and the impact of financial technology on young people ability to improve financial literacy. The urgency of this research is to find out the use of technology extent in the younger generation at the border regions of Indonesia in increasing knowledge about financial management. Because finance is one of the important factors in building economic resilience which is one of the national resilience pillars. This research conducted with qualitative method with phenomenology approach. The participants were younger generation whose between 17-35 years old based on WHO age classification. They came from Bengkayang, West Kalimantan. This research found a concept that there are 3 things to affect financial knowledge and the use of financial technology. These 3 things are the availability of technology, access to information, and environmental influences.